1993
DOI: 10.1128/jb.175.7.1995-2005.1993
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of bldA-specified tRNA is temporally regulated in Streptomyces coelicolor A3(2)

Abstract: Deletion of the bldA gene of Streptomyces coelicolor A3(2), which encodes the only tRNA for the rare UUA codon, had no obvious effects on primary growth but interfered with aerial mycelium formation and antibiotic production. To investigate the possible regulatory role of bldA, its transcription start point was identified, and time courses were determined for the appearance of its primary transcript, the processing of the primary transcript to give a mature 5' end, and the apparent efficiency of translation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 40 publications
5
119
0
1
Order By: Relevance
“…For actII-ORF4 (9), the actII-ORF4 promoter region included in a 635-base pair fragment (nucleotides 4824 -5458) was uniquely labeled at the 5Ј-end of the XhoI site (nucleotide 5458) within the actII-ORF4 coding region and was used as probe. RNA was extracted as described (61) from 3-day-old mycelium grown on the surface of cellophane discs on R5 agar plates as described (72).…”
Section: Methodsmentioning
confidence: 99%
“…For actII-ORF4 (9), the actII-ORF4 promoter region included in a 635-base pair fragment (nucleotides 4824 -5458) was uniquely labeled at the 5Ј-end of the XhoI site (nucleotide 5458) within the actII-ORF4 coding region and was used as probe. RNA was extracted as described (61) from 3-day-old mycelium grown on the surface of cellophane discs on R5 agar plates as described (72).…”
Section: Methodsmentioning
confidence: 99%
“…This inability of young Streptomyces cultures to efficiently translate UUAcontaining mRNAs suggests that the bldA tRNA may function to modulate the expression of key genes involved in sporulation and antibiotic production, as well as genes involved in other late developmental and metabolic processes. However, in contrast, studies by Gramajo et al (1993) found that functional bldA tRNA was present throughout growth in liquid cultures and did not show the temporal pattern of accumulation observed in both solid and in liquid grown cultures by Leskiw et al (1993). Therefore, there is still no firm evidence that bldA ' regulates ' translation of UUAcontaining mRNAs.…”
Section: Introductionmentioning
confidence: 69%
“…RNA was extracted from surfacegrown or liquid cultures as described elsewhere (Leskiw et al, 1993). Northern blot analysis of bldA and leuU transcripts was performed as previously described (Trepanier et al, 1997) [the probes for bldA, leuU and the 5S rRNA control were the oligonucleotides BKL5, BKL42 and BKL53 (Table 2), respectively, except that the hybridization temperature for the bldA probe was 37 mC].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A sequence analysis also revealed that both RapH and RapG contain the rare leucine codon TTA, which has been proposed to serve as part of the regulatory mechanism of secondary metabolites in Streptomyces. 60 Recently, the Biotica group showed that RapH and RapG have important roles as positive regulators in rapamycin biosynthesis. 23 Overexpression of rapH and rapG under the control of the ActII-ORF4/PactI activator/promoter in S. hygroscopicus enhanced the production of rapamycin by approximately 27-55% and 20-32%, respectively.…”
Section: Biological Activities Of Rapamycin and Its Analogsmentioning
confidence: 99%